Alterações observadas em radiografias simples do tórax de pacientes portadores de tuberculose pulmonar com baciloscopia positiva em Belo Horizonte - Jose Nelson Mendes Vieira (2009)
Objectives: To analyze and to describe chest radiographic findings in patients with pulmonary tuberculosis. Methods: Chest radiographies from 161 patients, diagnosed by sputum baciloscopy, at the public health service in Belo Horizonte, Brazil, were analyzed. Patients, 109 men and 52 women, aged 18 to 79 years. Radiographic descriptions were based on pulmonary localization (topography), radiological pattern (nodular, reticular, alveolar consolidation), presence of cavitation (number, localization, wall aspects), extrapulmonary abnormalities (mediastinal adenopathy, pleural effusion, pneumothorax). Results: Abnormalities were seen in 98,14% of radiographies. No isolated extrapulmonary finding was observed. Cranial regions of superior lobes as well as superior segment of inferior lobes were mostly affected. Multilobar involvements were the majority, especially with superior lobes. The nodular parenquimatous pulmonary were the most frequent pattern, followed by alveolar and reticular patterns. 76.58% of patients presented cavitary lesions, singles (47,11%) or multiples (52,89%), mostly at right upper lobe. Most cavities had thick walls (95,04%), regular inner surrounding (98,35%) and irregular outer surroundings (95,04%). Pleural effusions were seen at 4,35% of exams, mediastinal adenopathies in 3,73% and pneumothorax in 1,24%. Atypical presentations were not seen except an isolated lingula involvement. Discussion: All radiological findings were similar to the ones previously described in literature, except the nodular parenquimatous pulmonary pattern. Conclusions: Chest radiography should be considered a primordial procedure in tuberculosis propedeutics for its high sensitivity, low cost and feasibility. Nevertheless high quality of images is mandatory since allows early diagnosis and prevents disease progression and dissemination.